Analisis Ambiguitas Leksikal dan Gramatikal dalam Wacana Humor pada Akun Dagelan dan Nanangsptra di Platform Digital Instagram serta Pemanfaatannya sebagai Bahan Ajar di Sekolah Menengah Atas - Lian Nitami; Nanang Maulana; Meliyawati Meliyawati (Jurnal Bahastra, 2026)
The rapid development of digital media, particularly Instagram, has facilitated the proliferation of humorous discourse that frequently exploits linguistic ambiguity to produce comedic effects, posing interpretive challenges for students as active social media users. This study investigates the forms of lexical and grammatical ambiguity in humorous discourse on the Instagram accounts Dagelan and Nanangsptra and examines their potential as instructional materials for anecdotal texts in senior high schools. Employing a descriptive qualitative approach, data were collected through reading, observing, and note-taking techniques from posts published between February and April 2025, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that lexical ambiguity manifests in polysemy and homonymy, while grammatical ambiguity arises from word-formation processes and structurally similar phrases. These patterns indicate that digital humor discourse provides authentic and contextually relevant linguistic input. The study argues that integrating such materials into classroom instruction enhances students’ interpretive competence, language awareness, and critical thinking in understanding anecdotal texts.